Analisis Usahatani Sayur Selada (Lactuca Sativa L.) Pada Hidroponik Kita Di Kecamatan Ajung Jember - Anggraini, Dwi; Hadi, Syamsul; Aulia, Anisa Nurina (Indonesian Journal Publisher, 2025)
Intensive hydroponic lettuce farming will provide maximum production and profit, but this must be supported by how efficient the use of capital owned on the farm. The research objectives are (1) To analyze the lettuce cultivation system on Hidroponik Kita farm; (2) To analyze the amount of income on Hidroponik Kita farm; (3) To analyze the feasibility of farming on Hidroponik Kita. The method used in this research is qualitative method. Determination of the research area is done intentionally (Purposive Sample) namely in Ajung Village Ajung Keamatan Jember Regency. data analysis used in this research is quantitative descriptive analysis. The method of data analysis in this study using descriptive analysis and analysis of farm income, then continued with the R / C analysis to determine the feasibility of the business. The results showed; (1) The hydroponic lettuce cultivation system includes preparation, seeding, planting, maintenance and harvesting activities; (2) The income obtained from hydroponic lettuce farming is Rp. 36.197.409; (3) Analysis of the feasibility of hydroponic lettuce farming shows an R/C value of 1,99.